1982
DOI: 10.1136/adc.57.3.231
|View full text |Cite
|
Sign up to set email alerts
|

Timing of neonatal cerebroventricular haemorrhage with ultrasound.

Abstract: SUMMARY Sequential real-time ultrasound examinations were performed in 174 neonates to determine the time of occurrence of cerebroventricular haemorrhage (CVH). Of Real-time ultrasound equipment has assumed an important role in the detection of intraventricular haemorrhage in preterm infants. Since there is no known risk ofthe procedure and minimal disturbance to the neonate during its use, we considered it could be employed serially to time the occurrence of cerebroventricular haemorrhages (CVH) (that is ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…Haemorrhages and ischaemia may coexist in several infants, resulting in changes attributable to both. Thus after some time the extent of perinatal haemorrhagic or ischaemic trauma, or both to the preterm newborn's brain will be reflected by the presence of cystic lesions of the parenchyma and the size and shape of the ventricular system.1622 [27][28][29][30][31][32] Several studies have reported cranial ultrasound follow up in high risk preterm infants. 17 19 21 22 27 28 31 Most follow up, however, is limited to a few weeks or months while the infant is admitted to the neonatal unit.…”
Section: Resultsmentioning
confidence: 99%
“…Haemorrhages and ischaemia may coexist in several infants, resulting in changes attributable to both. Thus after some time the extent of perinatal haemorrhagic or ischaemic trauma, or both to the preterm newborn's brain will be reflected by the presence of cystic lesions of the parenchyma and the size and shape of the ventricular system.1622 [27][28][29][30][31][32] Several studies have reported cranial ultrasound follow up in high risk preterm infants. 17 19 21 22 27 28 31 Most follow up, however, is limited to a few weeks or months while the infant is admitted to the neonatal unit.…”
Section: Resultsmentioning
confidence: 99%
“…KOSMETATOS reports a statistical significant effect of mode of delivery through a multiple regression analysis [12]. The timing of IVH within the first day of life in the majority of cases [4] points at causal factors operating during labor, delivery and the first few hours of life. A pathogenetical model involving changes in cardio-respiratory function, changes in blood pressure and cerebral blood flow as well as a result of an impaired autoregulation has been commonly proposed [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The true timing of PIVH is a crucial information to an understanding of etiologic factors and their possible prevention [7,12]. Transfontanelle real-time ultrasonography (US) has been used as method of choice to detect and follow PIVH [14].…”
Section: Introductionmentioning
confidence: 99%